PKM bimbingan teknis akuntansi bagi pelaku Bank Perkreditan Rakyat Syariah sesuai SAK ETAP dan SAK Syariah di Sulawesi Selatan - Hariany Idris; Muhammad Anwar Kadir; Masnawaty Sangkala (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
This Community Partnership Program (PKM) is an implementation of community servise activities in Universitas Negeri Makassar. This is Accounting Training for Islamic Bank in Makassar. The purpose of this activity is the realization of an organization's financial governance that is economical, efficient, and effective. In the end, the community was able to participate financially with the maximum acceptance, which of course resulted in improved services. The Community Partnership Program Proposal Team has a background in Financial Accounting and Islamic Accounting. This background is very suitable and supports the implementation of the proposed program topic. Meanwhile, the costs used to implement this program are sourced from PNBP funds from Universitas Negeri Makassar with the implementation period in July 2019.